Improving rehabilitation motivation and motor learning ability of stroke patients using different reward strategies: study protocol for a single-center, randomized controlled trial - Zhao, Jingwang; Guo, Jiangling; Chen, Yeping; Li, Wenxi; Zhou, Ping; Zhu, Guangyue; Han, Peipei; Xu, Dongsheng (Frontiers in Neurology, 2024)
Background Stroke survivors often face challenges in motor learning and motivation during rehabilitation, which can impede their recovery progress. Traditional rehabilitation methods vary in effectiveness, prompting the exploration of novel approaches such as reward strategies. Previous research indicates that rewards can enhance rehabilitation motivation and facilitate motor learning. However, most reward paradigms have utilized fixed reward amounts, which also have limitations. Exploring alternative, more effective reward strategies, such as probabilistic rewards, is warranted to optimize stroke patient rehabilitation. Methods A total of 81 stroke patients will be recruited and randomly assigned to control, fixed reward, or probabilistic reward groups at a ratio of 1:1:1 using a randomized number table method. Participants will undergo 10 days of daily hand motor function rehabilitation training, with sessions lasting 20 min each. The training will involve pegboard tests and box and block tests. Control group participants will receive standard training, while fixed reward group members will receive monetary incentives for completing tests, and probabilistic reward group members will have the chance to win monetary rewards through a lottery box. Rehabilitation motivation and motor performance and functional near-infrared spectroscopy brain imaging will be conducted at designated time points. The primary outcome measure is the stroke rehabilitation motivation scale, and the second outcome measures include motor performance, simple test for evaluating hand function, motivation and pleasure scale self-report, and Pittsburgh rehabilitation participation scale. Discussion Reward-based training enhance rehabilitation participation and adherence, it also improve motor learning speed and memory retention of stroke patients. The fixed reward applied in the past studies could diminish the sensitivity of stroke patients to rewards, while probabilistic reward may provide unpredictable or variable incentives or reinforcements for motor rehabilitation. This study will compare the efficacy of different reward strategies in enhancing motor learning ability and rehabilitation motivation among stroke patients. By conducting a randomized controlled trial, the study seeks to provide valuable insights into optimizing stroke rehabilitation protocols and improving patient outcomes. Clinical Trial Registration:https://www.chictr.org.cn/, ChiCTR2400082419.